The Effect of Socio-Economic Changes in the Community on the Value and Face of Traditional Village Houses (Case Study: Tenganan Village, Karangasem Regency, Bali Province) - Verza Dillano Gharata; Widi Dwi Satria; Maqbul Kamaruddin (JURNAL ARSITEKTUR, 2022)
Tenganan Pegringsingan Village is located in the east of the island of Bali, especially in the Manggis District, Karangasem Regency. The Tenganan Pegringsingan Traditional Village is included in one of the "Bali Aga" or "Bali Mountains" villages located in Karangasem Regency. Tenganan Village has abundant cultural tourism and natural tourism. Since it was designated as a cultural tourism destination by the local government, there have been socio-economic changes for the people of Tenganan Village. These socio-economic changes have an impact on the values and faces of traditional village houses. Direct field observations, in-depth interviews, and spatial mapping of traditional houses were carried out in this study. Tourist destinations are so that they can be used as learning or input for Bali tourism villages in responding to tourism developments.